NILAI EKONOMI DAN PEMASARAN HASIL HUTAN BUKAN KAYU (HHBK) DI SEKITAR KAWASAN DAS WAE RIUAPA KABUPATEN SERAM BAGIAN BARAT - Hapid A Lessy; Rohny S Maail; Jusmy D Putuhena (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
The objectives of this study were to investigate the potential of NTFPs in forest areas around the Wae Riuapa watershed; calculating the value of economic benefits from the commodity of NTFPs that are cultivated by forest farmers around the Wae Riuapa watershed; and to examine the form of marketing of commodities of NTFPs which often carried out by forest farmers around the Wae Riuapa watershed. The results showed that the potential of NTFPs from this community around the Wae Riuapa watershed, namely: Resin, Lawang, Rattan, Fern, Bamboo, Pandanus, Agarwood, Orchid, Enau, Firewood, Honey, Birds, Wild Boar, Deer, Cassowary, Sago, Nutmeg, Cloves, Chocolate, Bananas & fruits. Grouping farmer income based on the type of livelihood which ranges from <Rp. 1,000,000, - Rp. 4,500,000 per family per year. Factors affecting the marketing aspect are market access and transaction processes for the selling price of commodities to be marketed, while the real problems in marketing in the study locations; Hunitetu, Rambatu, Rumberu and Rumahtita villages were the high prices of NTFsP commodity and the quite expensive of tranportatiom cost due to the market access has a high cost.